Opportunities and failures to prosecute violence against persons with disabilities at the international tribunals for the former Yugoslavia, Rwanda and Sierra Leone. (April 2023) - McInnes, Kate
Abstract: This paper presents an inexhaustive but thorough review of the evidence of violence against persons with disabilities that came before, or ought to have been known to, the prosecutors of the international criminal tribunals for the former Yugoslavia, Rwanda and Sierra Leone. This research demonstrates that despite significant and compelling evidence from investigators, journalists and witnesses, gross violations against persons with disabilities were largely ignored by the prosecution or treated merely as aggravating factors at sentencing. These crimes could instead have been characterized as an "other inhumane act" prosecutable as a crime against humanity, which would have emphasized the gravity of the crimes, provided recognition of the victims' suffering, imposed criminal sanctions on those responsible, and unequivocally condemned violence against persons with disabilities during armed conflict.